2008
DOI: 10.1128/aac.00036-08
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Ofloxacin-Resistant Mycobacterium tuberculosis Strains from Russia

Abstract: In this work, we studied the variation in the gyrA and gyrB genes in ofloxacin-and multidrug-resistant Mycobacterium tuberculosis strains circulating in northwest Russia. Comparison with spoligotyping data suggested that similar to the spread of multidrug-resistant tuberculosis, the spread of fluoroquinolone-resistant tuberculosis in Russia may be due, at least partly, to the prevalence of the Beijing genotype in a local population of M. tuberculosis.Fluoroquinolones (FQ) are potent second-line drugs recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
84
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 19 publications
(24 reference statements)
10
84
3
1
Order By: Relevance
“…Our data are in agreement with previous studies where FQ resistance was reported to be associated largely with mutations in codons 90 and 94 of gyrA (A90V, D94G, and D94Y [20,35]) and, more rarely, with mutations D94A, D94N, T80A, G88C, and D89 N gyrA (3,26,46). The distribution of mutations in the analyzed strains was in agreement with that reported in a recent study from St. Petersburg (26), suggesting a similar mechanism of drug resistance development in areas where the Beijing strains family dominates.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data are in agreement with previous studies where FQ resistance was reported to be associated largely with mutations in codons 90 and 94 of gyrA (A90V, D94G, and D94Y [20,35]) and, more rarely, with mutations D94A, D94N, T80A, G88C, and D89 N gyrA (3,26,46). The distribution of mutations in the analyzed strains was in agreement with that reported in a recent study from St. Petersburg (26), suggesting a similar mechanism of drug resistance development in areas where the Beijing strains family dominates.…”
Section: Discussionsupporting
confidence: 83%
“…The distribution of mutations in the analyzed strains was in agreement with that reported in a recent study from St. Petersburg (26), suggesting a similar mechanism of drug resistance development in areas where the Beijing strains family dominates. Mutations in gyrB are less common (3), and their association with resistance to FQ is not known.…”
Section: Discussionsupporting
confidence: 79%
“…19,21,42,46 Heteropeaks in fluoroquinolone-resistant M. tuberculosis have been described in detail previously. 48 In contrast to most bacteria, M. tuberculosis acquisition of drug resistance does not occur as a result of horizontal transfer of resistance-bearing genetic elements.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Substitutions Gly470Ala, Asn499Lys and D644+645 were never observed independently. 21,26,42 Systematic review…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation